2009
DOI: 10.1124/dmd.109.029710
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants ofCYP3A4andCYP3A5in Cynomolgus and Rhesus Macaques

Abstract: ABSTRACT:Cynomolgus and rhesus macaques are frequently used in preclinical trials due to their close evolutionary relationships to humans. We conducted an initial screening for genetic variants in cynomolgus and rhesus macaque genes orthologous to human CYP3A4 and CYP3A5. Genetic screening of 78 Indochinese and Indonesian cynomolgus macaques and 34 Chinese rhesus macaques revealed a combined total of 42 CYP3A4 genetic variants, including 12 nonsynonymous variants, and 34 CYP3A5 genetic variants, including nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 20 publications
2
56
0
Order By: Relevance
“…Several studies have demonstrated that monkeys are particularly useful in interspecies scaling for predicting human pharmacokinetics (Ward and Smith, 2004;Ward et al, 2005;Sakuda et al, 2006;Ogasawara et al, 2007). Recent studies have identified a number of P450 cDNAs from cynomolgus monkeys, including those of CYP3A8 and CYP3A5, which show high sequence identities (94 -95%) with the orthologous human CYP3A4 and CYP3A5, respectively (Uno et al, 2007(Uno et al, , 2010Iwasaki and Uno, 2009). Furthermore, when an oral dose of CYP3A substrates, such as midazolam (MDZ) and simvastatin, was coadministered with typical CYP3A inhibitors, these monkeys showed markedly higher plasma concentrations than those who received a dose of substrate alone (Kanazu et al, 2004;Ogasawara et al, 2007Ogasawara et al, , 2009a.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that monkeys are particularly useful in interspecies scaling for predicting human pharmacokinetics (Ward and Smith, 2004;Ward et al, 2005;Sakuda et al, 2006;Ogasawara et al, 2007). Recent studies have identified a number of P450 cDNAs from cynomolgus monkeys, including those of CYP3A8 and CYP3A5, which show high sequence identities (94 -95%) with the orthologous human CYP3A4 and CYP3A5, respectively (Uno et al, 2007(Uno et al, , 2010Iwasaki and Uno, 2009). Furthermore, when an oral dose of CYP3A substrates, such as midazolam (MDZ) and simvastatin, was coadministered with typical CYP3A inhibitors, these monkeys showed markedly higher plasma concentrations than those who received a dose of substrate alone (Kanazu et al, 2004;Ogasawara et al, 2007Ogasawara et al, , 2009a.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study also found many genetic variants in a large number of genes were shared between the two lineages [13], including CYP3A4 and CYP3A5 [15]. On the other hand, 12 and 5 genetic variants were unique to cynomolgus and rhesus macaques, respectively (Table 2).…”
mentioning
confidence: 77%
“…Expression of macaque CYP1B1 mRNA has been detected in brain regions, including frontal cortex, hippocampus, thalamus, and amygdala [8]. Since macaques have a diverse genetic background, similar to human, as evidenced by identification of genetic variants in a number of genes, including CYPs [15,16], macaques might possess numerous CYP1B1 genetic variants. Some variants could account for inter-animal differences in CYP1B1-dependent metabolism of promutagens, making it difficult to interpret the data obtained.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Macaque CYP3A8(4) metabolizes typical human CYP3A4 substrates such as midazolam and nifedipine (Iwasaki et al, 2010;Uno et al, 2010) and is induced by the typical human CYP3A4 inducer, rifampicin (Kim et al, 2010), indicating that CYP3A8(4) has drug-metabolizing enzyme properties similar to human CYP3A4. Induction of cynomolgus macaque CYP3A8(4) and human CYP3A4 by rifampicin is mediated via PXR (Kim et al, 2010), which binds to the regulatory element in the upstream region of CYP3A4, suggesting that the regulatory region of cynomolgus macaque CYP3A8(4) and human CYP3A4 is conserved well between macaque and human.…”
Section: Estradiol-regulated Drug-metabolizing Enzymes In Macaquementioning
confidence: 99%